HUBUNGAN EXPLOSIVE POWER OTOT TUNGKAI DENGAN LOMPAT TINGGI PADA SISWA KELAS X SMN 1 SIAK KECIL - ', Istiyani; ', Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problems of the research is the lack of explosive power of leg muscles in performing maximum jump. To get a powerful push and high speed, an athlete should have huge explosive power. So, the explosive power of leg muscles should as a pushing power of a jump while doing a push on the ruler after doing the initial act to get maximum jump. Therefore, explosive power of leg muscles has a meaningful contribution while an athlete will perform jumping move in High Jump sport. Based on the observation by the researchers in the field, the result of the jump of the students, especially class ten of SMAN 1 Siak Kecil with 25 students as population and all of 25 students as sample. suharsimi-arikunto(2006:13) says if the subject is less than 100 people, then the whole subject of more then 100 people then take or use 20-25% of the whole sampel. The technique of sample collection is all of the population (Total sampling). The instrument used in this research is Vertical Jump which is aimed at discovering the jump result, and High Jump test that is aimed at maximizing the jump. Afterward, the data is analyzed statistically to examine the normality by lilifors test by the significant rate of 0.05 α. The hypothesis proposed is that there is a significant correlation between the power of leg muscles and High Jump. Based on the analysis of lilifors tegst Lcount (x) is 0.164 and Ltable is0.173, Lcount (y) is 0.164 dan Ltable is 0.173 which mean that Lcount < Ltable, so the samples form the population that has a normal distribution. Then the result of Product Moment correlation between leg muscle power and shoulder and the result of smash accuracy where rcount(0.752) > rtable (0.404) which resulted that Ho is accepted and Ha is rejected. Therefore, there is a significant influence between leg muscle explosive power and High Jump of Ten grade students at SMAN 1 Siak Kecil. Keywords: Leg Muscle Explosive Power, High Jump